The accuracy of automatic and human live captions in English - Romero-Fresco, Pablo; Fresno, Nazaret (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2023)
Closed captions play a vital role in making live broadcasts accessible to many viewers. Traditionally, stenographers and respeakers have been in charge of their production, but this scenario is changing due to the steady improvements that automatic speech recognition has undergone in recent years. This technology is being used to create intralingual live captions without human assistance and broadcasters have begun to explore its use. As a result, human and automatic captions co-exist now on television and, while some research has focused on the accuracy of human live captions, comprehensive assessments of the accuracy and quality of automatic captions are still needed. This article airs this matter by presenting the main findings of the largest study conducted to date to explore the accuracy of automatic live captions. Through four case studies that included approximately 17,000 live captions analysed with the NER model from 2018 to 2022 in the United Kingdom, the United States, and Canada, this article tracks the recent developments with unedited automatic captions, compares their accuracy to that achieved by human beings, and concludes with a brief discussion of what the future of live captioning looks like for both human and automatic captions.